Students perception on social entrepreneurship education in higher education institutions (HEIs) - Radin A Rahman, Radin Siti Aishah; Lope Pihie, Zaidatol Akmaliah (International Educative Research Foundation and Publisher, 2015)
Education can play a role in heightening the development of social entrepreneurship (SE) knowledge and skills in a developing country. Malaysia is amongst countries with undesirably low achievement level in the overall social entrepreneurship activity. Hence, efforts need to be enhanced so that the younger generation would be more inclined and motivated to partake in social entrepreneurship to contribute to the existing added value that students already possess. The early cultivation of social entrepreneurship can be detected through informal exposure by students who are actively involved in voluntary projects and developmental community club called ENACTUS. Apart from that, some higher education institutions are offering subjects and short term projects related to social entrepreneurship. The efficacy of SE education will be a yard stick to ensure that more prospective social entrepreneurs are produced in the future. Therefore, a descriptive research has been conducted on 350 ENACTUS members using stratified sampling to explore students and alumni perception on social entrepreneurship. Findings showed that a majority of students agreed if SE education is made a compulsory course in HEI. However, the alumni did not agree with this idea. Although many students and Alumni admitted that they understand the social entrepreneurship concept, nevertheless there are a select few who could not complete their main goal when managing ENACTUS projects. Therefore, they were unable to make their ideologies run concurrently with goals of the projects. This article will attempt to discuss the implications of cultivating the social entrepreneurship culture.